Strictly positive solutions for one dimensional nonlinear elliptic problems - Kaufmann, Uriel; Medri, Iván Vladimir (2021)
Fil: Kaufmann, Uriel. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.